Insights on Molecular Mechanisms of Ovarian Development in Decapod Crustacea: Focus on Vitellogenesis-Stimulating Factors and Pathways - Jayasankar, Vidya; Tomy, Sherly; Wilder, Marcy N. (Frontiers in Endocrinology, 2020)
Vitellogenesis in crustaceans is an energy-consuming process. Though the underlying mechanisms of ovarian maturation in decapod Crustacea are still unclear, evidence indicates the process to be regulated by antagonistically-acting inhibitory and stimulating factors specifically originating from X-organ/sinus gland (XO/SG) complex. Among the reported neuromediators, neuropeptides belonging to the crustacean hyperglycemic hormone (CHH)-family have been studied extensively. The structure and dynamics of inhibitory action of vitellogenesis-inhibiting hormone (VIH) on vitellogenesis have been demonstrated in several species. Similarly, the stimulatory effects of other neuropeptides of the CHH-family on crustacean vitellogenesis have also been validated. Advancement in transcriptomic sequencing and comparative genome analysis has led to the discovery of a large number of neuromediators, peptides and putative peptide receptors having pleiotropic and novel functions in decapod reproduction. Furthermore, differing research strategies have indicated that neurotransmitters and steroid hormones play an integrative role by stimulating neuropeptide secretion, thus demonstrating the complex intertwining of regulatory factors in reproduction. However, the molecular mechanisms by which the combinatorial effect of eyestalk hormones, neuromediators and other factors coordinate to regulate ovarian maturation remain elusive. These multifunctional substances are speculated to control ovarian maturation possibly via the autocrine/paracrine pathway by acting directly on the gonads or by indirectly exerting their stimulatory effects by triggering the release of a putative gonad stimulating factor from the thoracic ganglion. Acting through receptors, they possibly affect levels of cyclic nucleotides (cAMP and cGMP) and Ca2+ in target tissues leading to the regulation of vitellogenesis. The “stimulatory paradox” effect of eyestalk ablation on ovarian maturation continues to be exploited in commercial aquaculture operations, and is outweighed by the detrimental physiological effects of this procedure. In this regard, the development of efficient alternatives to eyestalk ablation based on scientific knowledge is a necessity. In this article, we focus principally on the signaling pathways of positive neuromediators and other factors regulating crustacean reproduction, providing an overview of their proposed receptor-mediated stimulatory mechanisms, intracellular signaling, and probable interaction with other hormonal signals. Finally, we provide insight into future research directions on crustacean reproduction as well as potential applications of such research to aquaculture technology development.